Barrier height tuning in Ti/4H-SiC Schottky diodes. (December 2021) - Bellocchi, G.; Vivona, M.; Bongiorno, C.; Badalà, P.; Bassi, A.; Rascuna', S.; Roccaforte, F.
Highlights: Controlling of Schottky barrier in SiC diodes. Effect of temperature on the Schottky contact quality and barrier height. Effect of thickness of the Schottky contact in quality and height of the barrier. Abstract: In this work, we investigated the effects of annealing temperature and metal thickness on the Schottky barrier height in state-of-the-art Ti/4H-SiC rectifiers. By varying these two parameters, a controlled lowering of the Schottky barrier height has been obtained, thus giving the possibility to improve the efficiency of device in terms of power consumption.